Emerging Three-Dimensional Hepatic Models in Relation to Traditional Two-Dimensional In Vitro Assays for Evaluating Drug Metabolism and Hepatoxicity - Erin Milner; Michael Ainsworth; Matthew McDonough; Benjamin Stevens; Johannah Buehrer; Richard Delzell; Cameron Wilson; Jason Barnhill (Elsevier, 2020)
A vital aspect of preclinical drug development involves assessing hepatic metabolism and toxicity. These screenings are typically conducted utilizing in vitro assays and in vivo animal models; however, recent advancements in tissue engineering offer a hybrid approach to augment current protocols. Three dimensional (3D) bioprinting has enabled the creation of assays that offer a more accurate model of human physiology, especially in the realm of hepatotoxicity. Herein we review and compare current 2D and 3D hepatic models and assess their pros and cons. While two dimensional (2D) in vitro assays continue to serve as efficient, low-cost and high-throughput screening tools to assess hepatotoxicity prior to in vivo studies, recent advances in 3D methods are delivering improved analysis of the complex in vivo microenvironment.